Penggunaan Model Pembelajaran Problem-Based Learning untuk Meningkatkan Mutu Akhlak Peserta Didik - Tarjono, Tarjono; Nurzaman, Nurzaman (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
Model of moral cultivation in MTsN Bangunharja done using three methods, classical cultivation methods, extra-curricular activities in the form of religious activities, scouting, sports, and Islamic art, and habituation of morals. Problem base learning model in MTsN Bangunharja applied using the following steps: find the problem, define the problem, determine the facts, develop provisional estimates, investigate, enhance the problem has been defined, concluded alternatives to solving collaboratively, test solutions to problems. The problem base learning and teaching model is proven to improve the quality of the character of students in MTsN Bangunharja. This is evidenced by the results of statistical calculations that generate t values of 26.35, while t table amounted to 1.7109.